Successful multiple Percutaneous Interventions and Biventricular Surgical Repair in a Child with Pulmonary Atresia with Intact Ventricular Septum— A Case Report (Cardiovascular Journal, 2020)
Pulmonary atresia (PA) with intact ventricular septum is a rare, heterogeneous congenital heart defect with varying degrees of right ventricular and tricuspid valve hypoplasia and wide spectrum clinical features. Initial treatment at presentation is to establish systemic to pulmonary shunt or ductus stenting. The treatment options i.e. biventricular, one and half ventricular or one ventricular repair are often dictated by the degree of development of the tricuspid valve and right ventricle. X, 11 years old teenage girl got admitted to Combined Military Hospital (CMH) Dhaka at 5 months of age with severe cyanosis, respiratory distress, acidosis and shock. After immediate stabilization and work up, she was diagnosed as pulmonary atresia with intact ventricular septum, flapped atrial septal defect (ASD) and a small patent ductus arteriosus (PDA). On urgent basis, stenting of PDA done with 3.5 X 11 mm coronary stent at cardiac catheterization laboratory. Her SPO2 stepped up to 90 % from base line SPO2 from 50% following procedure. At 15 months of age she underwent intracardiac repair with short trans annular patch and ASD left open as a vent for RV. On follow up her ASD was getting larger and became desaturated and symptomatic. She was followed up for the right ventricular (RV) and tricuspid valve growth and ASD shunt. As her RV was developing nicely during follow up and achieved TV z score –1, ASD device closure was done with 18 mm Amplatzer ASD device at 5 years of age. She is now asymptomatic and thriving well.Cardiovasc. j. 2020; 13(1): 81-85